TRANSFORMASI KELEMBAGAAN PADA DINAS KETAHANAN PANGAN DAN PERTANIAN KABUPATEN BOJONEGORO - Fatma Nur Arofah; Arimurti Kriswibowo (Universitas Bina Taruna Gorontalo, 2024)
This research aims to determine the institutional transformation process at the Bojonegoro Regency Food Security and Agriculture Service, which is a new regional apparatus organization that was formed through a merger/merger process based on Bojonegoro Regent Regulation No. 85 of 2021. The Bojonegoro Regency Government is trying to streamline the main duties of the two agencies by combine/merger to create an agile organizational structure. Through the merger process, of course there were many changes in function and structure. This change in structure and function is the background for the need for scientific research regarding organizational changes which previously merged two different OPDs to form one new OPD. The method used is descriptive qualitative research with a case study approach. The results of the research found that the Bojonegoro Regency Food and Agriculture Security Service has carried out organizational transformation through strengthening the vision and mission, changing the organizational structure, improving public services through online applications and websites, building partners with other parties and implementing a reward and punishment system for employees.